Realising the Right to Electricity Through Off-Grid Power Solutions in South Africa - Germarie Viljoen; Felix Dube (Potchefstroom Electronic Law Journal, 2023)
The South African government is navigating many basic municipal service delivery challenges, including a growing electricity supply deficit. Eskom Holdings SOC Limited, the state-owned power utility, is struggling to generate and supply a stable and uninterrupted flow of electricity through its grid system. The inadequate generation capacity results in rotating power outages, known as loadshedding, which occur when demand surpasses generating capability. This fundamental service delivery challenge, in conjunction with South Africa's climate change responses, including the decision to work towards energy efficiency, renewable energy and cleaner energy or a "just transition" from coal to clean energy, encourages many South Africans who have the necessary means to invest in off-grid energy solutions that operate alongside and at times independently of Eskom's grid. This paper considers from a legal perspective how and to what extent legislation on electricity supply and municipal by-laws empower household consumers to fulfil their right to electricity by going off-grid. The paper ultimately considers the import of this on South Africa's energy governance framework for electricity provision in the country.